Stored Canine Whole Blood Units: What is the Real Risk of Bacterial Contamination?. (13th October 2016) - Miglio, A.; Stefanetti, V.; Antognoni, M.T.; Cappelli, K.; Capomaccio, S.; Coletti, M.; Passamonti, F.
Abstract : Background: Bacterial contamination of whole blood (WB) units can result in transfusion‐transmitted infection, but the extent of the risk has not been established and may be underestimated in veterinary medicine. Objectives: To detect, quantify, and identify bacterial microorganisms in 49 canine WB units during their shelf life. Animals: Forty‐nine healthy adult dogs. Methods: Forty‐nine WB units were included in the study. Immediately after collection, 8 sterile samples from the tube segment line of each unit were aseptically collected and tested for bacterial contamination on days 0, 1, 7, 14, 21, 28, 35, and 42 of storage. A qPCR assay was performed on days 0, 21, and 35 to identify and quantify any bacterial DNA. Results: On bacterial culture, 47/49 blood units were negative at all time points tested, 1 unit was positive for Enterococcus spp. on days 0 and 1, and 1 was positive for Escherichia coli on day 35. On qPCR assay, 26 of 49 blood units were positive on at least 1 time point and the bacterial loads of the sequences detected ( Propionobacterium spp., Corynebacterium spp., Caulobacter spp., Pseudomonas spp., Enterococcus spp., Serratia spp., and Leucobacter spp.) were <80 genome equivalents (GE)/μL. Conclusions and Clinical Importance: Most of the organisms detected were common bacteria, not usually implicated in septic transfusion reactions. The very low number of GE detected constitutes an acceptable risk of bacterial contamination, indicating that WB units have a good sanitary shelf life during commercial storage.